CRIMINOLOGICAL CHARACTERISTICS OF VIOLENT CRIMINAL OFFENSES IN THE COMBAT ZONES - ZARADIUK, ZORIANA (Ehrlich's Journal, 2025)
The article analyzes the main aspects of the criminological characteristics of violent criminal offenses in the areas of hostilities. The author emphasizes that violent criminal offenses on the territory of Ukraine are characterized by unprecedented cruelty and large scale. The article defines the concept of violent criminal offenses in the areas of hostilities and identifies their main determinants. The article also identifies the main areas of hostilities and provides statistics on violent war crimes since the beginning of the full-scale invasion. According to the author, in order to effectively protect against violent crimes in combat zones, it would be worthwhile to make several changes to the legislation of Ukraine, including the adoption of a law on human rights organizations operating in combat zones; amendments to the Criminal Executive Code to regulate the status of treatment of prisoners in combat zones; and expansion of mechanisms for protecting victims of violence in combat zones. These crimes are complex in nature, including both war crimes and general criminal offenses. They pose serious challenges for law enforcement and the judiciary, as well as for the protection of human rights in armed conflict. The article describes the criminological profile of criminals who commit violent crimes in the combat zone: usually a young or middle-aged man, approximately 20 to 40 years old. Young people usually have more pronounced aggressiveness and a greater propensity for violence, especially in conditions of stress or social maladjustment that may arise during war. Criminals committing violent crimes in combat zones have a complex motivation that includes psychological, ideological and social factors. Their actions can be caused by both individual characteristics and environmental influences.